PENGARUH PEMBERIAN INSENTIF PAJAK DI TENGAH PANDEMI CORONA TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM PELAPORAN SURAT PEMBERITAHUAN (SPT) (Studi Kasus Pada KPP Malang Utara) - Dhuratun Nuskha; Nur Diana; Dwiyani Sudaryanti (Universitas Islam Malang, 2021)
This study aims to determine the effect of tax incentives in the midst of the corona pandemic on the level of compliance of individual taxpayers in tax returns (SPT) reporting. The research method used is quantitative correlational with simple linear regression method. Data collection in this study was carried out by distributing questionnaires in the form of google form to individual taxpayers registered at KPP Malang Utara. Sampling using the Slovin formula by means of purposive sampling. Purposive sampling is sampling that is carried out based on considerations in accordance with the purpose of the study. From the calculation of the Slovin formula, there were 100 respondents. The results showed that the tax incentive variable had a positive and significant effect on the taxpayer compliance variable. Keywords: Tax incentives, individual taxpayer compliance, SPT reporting